2020
DOI: 10.1080/09718524.2020.1829359
|View full text |Cite
|
Sign up to set email alerts
|

Use of the infection and treatment method in the control of East Coast fever in Kenya: does gender matter for adoption and impact?

Abstract: East Coast fever (ECF), caused by a protozoon and transmitted by ticks, is the most critical cattle disease in Eastern and Southern Africa. Farmers have used the Infection and Treatment Method (ITM) to control ECF in Kenya since 2012. Yet, the differences in terms of perceptions and benefits accrued between men and women remain unclear. This study sought to understand how men and women perceive ITM effectiveness and to evaluate its impact on their livelihoods. The study included 29 gender-disaggregated focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…While the previous results had shown that more feed purchases increase herd productivity, the longer-term reverse causal link of ITM vaccination, representing a higher production potential, stimulating a greater use of feed inputs could not be detected. This also applies to the off-take rate and the share of herds with improved breeds, despite previous findings on changes in breed composition by ITM adopters (18). In addition, clearly differentiating animals of local breeds, which are often genetically mixed, from improved cross-bred animals is challenging in a survey situation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While the previous results had shown that more feed purchases increase herd productivity, the longer-term reverse causal link of ITM vaccination, representing a higher production potential, stimulating a greater use of feed inputs could not be detected. This also applies to the off-take rate and the share of herds with improved breeds, despite previous findings on changes in breed composition by ITM adopters (18). In addition, clearly differentiating animals of local breeds, which are often genetically mixed, from improved cross-bred animals is challenging in a survey situation.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the same study reports that vaccinated animals, identified by their ear-tags, fetched higher prices at cattle markets. Furthermore, a trend toward improved cattle breeds has been reported where ITM has been adopted in extensive systems ( 18 ). In intensifying dairy systems, the use of the ITM vaccine allows farmers to quickly reduce the frequency of tick control (from weekly or twice weekly dipping/spraying regimes to once in 2 or 4 weeks, which is still required to control other tick-borne diseases) without any detrimental animal health effects ( 32 ), cited in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…These results were expected, since studies have shown that empowering women in agriculture tends to increase their ability to earn and control income from agricultural enterprises (Galab & Rao 2003). In addition, women have been shown to channel most of their income to improving household nutrition (buying nutritious food such as animal source food) and general household development, such as buying clothes, constructing better shelters and educating their children (Greene 2003;Tsiboe et al 2018;Galiè et al 2019;Jumba et al 2020;Opata et al 2020). A study in Nigeria shows that women's empowerment leads to an improvement in children's anthropometric scores (Aderemi 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A study done in the sugarcane growing regions in western Kenya showed that women in male-headed households are discriminated against when it comes to control over sugarcane income, and this is mainly due to patriarchal systems and norms and taboos that gave men more power over family assets (Kwenya et al 2021). Empirical evidence shows that women are the main providers of labour in agricultural enterprises in sub-Saharan African (SSA) (Theis et al 2018;Jumba et al 2020), and this could be the reason why poor work balance is a major contributor to the disempowerment of women in sugarcane farming.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of the impact of livestock interventions on indicators of women’s empowerment, the most common negative consequence was an increase in women’s workload ( 27 ), as reported by a dairy intensification project in Uganda, for example ( 28 ). Family members who do not see the benefits of an innovation may oppose its adoption in the household, undermining the effectiveness of an intervention, as in the case of East Coast Fever infection and treatment method in Kenya ( 29 ). Increase in workload can be an acceptable change if it brings commensurate benefits ( 30 ).…”
Section: Gender Considerations In One Healthmentioning
confidence: 99%